Investigation of key aspects for the successful marketing of cowpeas in Senegal - Faye, Mbene Dieye (University of the Free State, 2004)
Due to the lack of information on the factors that affect the marketing of cowpeas in Senegal, this study investigates key aspects for the successful marketing of cowpeas in Senegal. The contribution this study makes lies in the information it generates to empower role-players in the cowpea value chain to better understand (i) the demand relations of cowpeas in Senegal, (ii) the information needs of role-players and the extent to which markets are integrated, and (iii) for which characteristics of cowpea consumers are willing to pay premiums. An Almost Ideal Demand System (AIDS) model is applied to one period cross sectional data to estimate demand relations of cowpea’s in Senegal. The own price elasticity of cowpea is -1.23 while its expenditure elasticity is 0.97 showing that cowpea is a normal necessity. A sample of 443 respondents was taken to determine the information needs of different role-players in the cowpea supply chain. Availability of price information on local and export markets are deemed vitally important by all role players. Information pertaining to quantities supplied and demanded, and buyers’ preferences are not regarded by all role-players as equally important. The most appropriate mode to dissemination cowpea related information should depend on the accessibility of a particular mode by role-players. Bivariate correlation coefficients, co-integration tests, Granger Causality tests and Ravallion’s model are used to investigate level of market integration. The results show that cowpea markets as a whole are not integrated. This is not a surprising result since it can be linked to the general lack of market information. The influence of cowpea characteristics on cowpea prices is analyzed with a hedonic pricing model. The results show that large grain size and sugar contents are characteristics for which consumers are willing to pay premiums in all markets. The implication of the results of this study has several dimensions, i.e. (i) role-players in the cowpea supply chain now has information to guide pricing strategies, (ii) changes in expenditures on cowpeas can be properly discounted in marketing strategies, (iii) interventions can be designed to address the needs of information users and to address the non-integrated nature of cowpeas markets, and (iv) research programs and role-players should focus their research and marketing activities on those characteristics for which consumers are willing to pay premiums.
Keywords: Thesis (Ph.D. (Agricultural Economics))--University of the Free State, 2005; Cowpea -- Senegal -- Marketing; Cowpea -- Economic aspects; Dried beans -- Senegal -- Marketing